Approach for use of acceleration values for packages of radioactive material under routine conditions of transport. (December 2013) - Apel, A.; Ballheimer, V.; Kuschke, C.; Schubert, S.; Wille, F.
<x content-type="archive" xml:space="preserve">Abstract</x> The most relevant source of reference for load cases of packages for the transport of radioactive material under routine conditions is Appendix IV of the International Atomic Energy Agency (IAEA) Advisory Material TS-G-1·1. The acceleration values given there leave many questions open and have to be agreed upon with the involved competent authorities. Consequently, the actual load cases applied for a safety analysis may differ widely and could cause problems for international transport. To avoid such difficulties, it seems obvious that the according passages in TS-G-1·1 should be modified with the objective of making the load case data more consistent for a harmonized application in the IAEA member states. Papers pointing out in this direction were discussed at the PATRAM 2010 conference. The way to improve the acceleration data may lie in investigations and measurements considering, for example different types of vehicles and package masses. However, what should be the goal of such kind of surveys? Can such investigation provide values for every worldwide load case possible under routine conditions of transport? In particular, the different designs of vehicles give a reason to doubt that such an aim is realistic. The approach in this paper is to show that a less ambitious aim is more effective. Therefore, an approximate scheme is preferred, which renders better assistance in determining the appropriate acceleration values.